"In the back of my mind, time always ticks one hour forward": The transnational temporalities of Moldovan domestic workers in Italy. Issue 5 (20th November 2020) - Cojocaru, Olga
Abstract: This article analyses the temporalities of transnational living through a threefold frame: as an outlook, as a resource and as a qualitative experience. Drawing on data from interviews with Moldovan women who are domestic workers in Italy, I point to the time work employed by these labour migrants to navigate a multitude of timescapes derived from a (permanently) temporary status, precarious resources and the emotional ambivalence that arises from being away from their families. I show how migrants' envisioned temporariness of transnational living materialises into a time‐bound outlook, which, in turn, compels them to manage time as a scarce resource, that has to be managed, planned and worked with. Lastly, I indicate that maintaining a temporary outlook correlates with a halting strategy and may have significant effects on personal and family well‐being.